How Do Major World Event Affect the Stock Market: Connecting stock market fluctuations with political events (Journal of Advances and Scholarly Researches in Allied Education, 2017)
This paper seeks to examine how the stock markets around the world react to changes, whether gentle or turbulent, in the wake of any major event; political or as an act of terrorism in any particular country. It aims to connect the stock market movements in a particular country with the political winds blowing in that country, and will seek to infer whether the fluctuations in the market are caused as a direct result of any major political event, or whether the stock market is largely indifferent to any political scenario, current or potential.